The Role And Evolution Of Computer Technology In Military Strategy: A Perspective From The World War II Era To The Contemporary Cyber Warfare Era - Maesaroh, Siti; Isneni, Syilmi; Adventius.P.H, Nathanael Aurick (Journal Collabits, 2024)
Computer technology has become a crucial element in military strategy from the World War II era to the contemporary Cyber War era. During World War II, early computers were used to crack enemy encryption codes and optimize the trajectories of artillery projectiles. As development progressed, electronic computers emerged, providing faster and greater computing capabilities. In the Cold War era, computers were used in war simulations and the development of missile defense systems. Then, with the advent of the Cyber War era, computer technology became central to military operations, used in cyber monitoring and defense, intelligence analysis, and network operations. The transformation of computer technology from mainframe computers to global networks has changed the landscape of modern warfare, enabling the development of sophisticated cyber weapons and tactics. In this context, this article reviews the use and transformation of computer technology in military strategy from World War II to contemporary Cyber Warfare, highlighting the key role of computers in shaping the dynamics of modern warfare.